Effects of walking training with blood flow restriction on the hemodynamics and perceptual responses among sedentary college students: A randomized crossover trial - Yuke Zhu; Ying Wang; Siyu Yu; Dejiang Sun; Xiuyi Ji; Wenbin Yuan; Min Ma; Huagang Hu (PLoS ONE, 2026)
College students often present a sedentary lifestyle. Low-intensity walking training with blood flow restriction (WT-BFR) may offer health benefits comparable to moderate-to-high intensity walking training without restriction, yet its effects in sedentary college students remain unclear. This study aimed to examine the effects of WT-BFR at different limb occlusion pressure (LOP) on hemodynamic and perceptual responses in sedentary college students using a randomized crossover design. The study was registered on the China Clinical Trial Registry (ChiCTR2500097728 25/02/2025). A total of 60 participants completed the 5-minute WT-BFR with varying LOPs (i.e., 0%, 40%, 60%, and 80%). Hemodynamic parameters (blood pressure and heart rate) were measured before, immediately after, and 5 minutes post-intervention. Meanwhile, perceptual responses (perceived exertion and discomfort) and step numbers were recorded post-intervention. For the hemodynamic parameters, only 60% LOP showed a larger increase in heart rate after training than 0% LOP (walk training without BFR) condition (3.82, 95%CI: 0.72 to 6.91, p = 0.016, beats/min), representing a relative increase of approximately 5.6% from baseline. With the increase of LOP, perceived exertion and discomfort were increased significantly (p < 0.05), and the step numbers were reduced (p < 0.05). Based on participant perception, an LOP range of 40%–60% is recommended. Clinically, the observed cardiovascular changes were modest and within safe ranges for healthy young adults. The long-term health effects of low-intensity WT-BFR among college students warrant further investigation.